Determinants of access to chronic illness care: a mixed-methods evaluation of a national multifaceted chronic disease package for Indigenous Australians. Issue 11 (27th November 2015) - Bailie, Jodie; Schierhout, Gill; Laycock, Alison; Kelaher, Margaret; Percival, Nikki; O'Donoghue, Lynette; McNeair, Tracy; Bailie, Ross
Abstract : Objectives: Indigenous Australians have a disproportionately high burden of chronic illness, and relatively poor access to healthcare. This paper examines how a national multicomponent programme aimed at improving prevention and management of chronic disease among Australian Indigenous people addressed various dimensions of access. Design: Data from a place-based, mixed-methods formative evaluation were analysed against a framework that defines supply and demand-side dimensions to access. The evaluation included 24 geographically bounded 'sentinel sites' that included a range of primary care service organisations. It drew on administrative data on service utilisation, focus group and interview data on community members' and service providers' perceptions of chronic illness care between 2010 and 2013. Setting: Urban, regional and remote areas of Australia that have relatively large Indigenous populations. Participants: 670 community members participated in focus groups; 374 practitioners and representatives of regional primary care support organisations participated in in-depth interviews. Results: The programme largely addressed supply-side dimensions of access with less focus or impact on demand-side dimensions. Application of the access framework highlighted the complex inter-relationships between dimensions of access. Key ongoing challenges are achieving population coverage through a national programme, reaching high-need groups and ensuring provision of ongoing care. Conclusions: Strategies to improve access to chronic illness care for this population need to be tailored to local circumstances and address the range of dimensions of access on both the demand and supply sides. These findings highlight the importance of flexibility in national programme guidelines to support locally determined strategies.